Evaluation of aortic changes in elderly people autopsied with acquired immunodeficiency syndrome - Mariana Silva Oliveira; Bianca Gonçalves Silva Torquato; Luciano Alves Matias da Silveira; Gabriela Ribeiro Juliano; Laura Sanches Aguiar; Guilherme Ribeiro Juliano; Lívia Ferreira Oliveira; Ana Paula Espindula; Luciana Santos Ramalho; Camila Lourencini Cavellani; Aline Cristina Souza da Silva; Grace Kelly Naves de Aquino Favarato; et al. (BMC, 2018)
Abstract Background To verify the distribution of the degree of fat deposits and percentage of collagen and elastic fibers in the intimal and medial layers of the aorta of elderly patients autopsied, with and without Acquired Immunodeficiency Syndrome (AIDS). Methods Twenty-six fragments of the aorta from elderly patients autopsied in the period from 1982 to 2014, were collected and, divided into two groups, being 13 with AIDS and 13 without AIDS. The intensity of the atherosclerosis was macroscopically evaluated in a semi-quantitative way. To quantify the elastic and collagen fibers, it was used the Leica Qwin Plus® software. Results In the comparison of the macroscopic intensity of atherosclerosis, the AIDS group (t = 0.6969, p = 0.4992). Regarding elastic fibers, there was a significant increase in the AIDS group (U = 115,800; p < 0.0001). Comparing the groups, there was a significant increase of the collagen fibers in the aortic layers in the AIDS group (U = 114,100; p < 0.0001). Conclusion The infection by the HIV influence in the amount of fibers in the extracellular matrix and the intensity of lipid deposit, demonstrating that it may be a risk factor to be considered for the development of atherosclerosis.